Uji Organoleptik Dan Kandungan Nutrisi Biskuit Dengan Bahan Fortifikasi Tepung Kelor (Moringa oleifera) Untuk Penanganan Stunting - Melissa Syamsiah; Yuliani; Angga Adriana Imansyah; Riza Trihaditia (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2022)
Stunting is a nutritional problem caused by chronic malnutrition. Nutrition and nutritional intake for people affected by stunting, especially toddlers, can be obtained through the consumption of healthy and nutritious food. Biscuits are a food that is loved by all groups, especially toddlers. Moringa has many benefits, especially for health and medicine. The addition of Moringa flour fortification can increase the nutritional value of biscuits. This study aims to determine the results of the preference test (organoleptic) of biscuits with fortified moringa flour, and to compare the nutritional content of biscuits from the best fortified formulation with biscuits without the addition of moringa flour. The research was conducted in September - November 2022 at the Teaching Factory of the Faculty of Applied Science, Suryakancana University and the Laboratory of the Center for Agro Industry. This study used treatment in the form of the addition of moringa flour fortification: 0%, 1%, 2%, 3%, 4% and 5%. Organoleptic test through hedonic/liking test was conducted on 25 panelists and 2 expert panelists. The nutritional test was carried out on biscuits with the best organoleptic test results with biscuits without the addition of moringa flour as a control. The results showed that the A2 treatment (addition of 2% moringa flour) was the treatment that gave the most recommended organoleptic test results for consumption. Furthermore, the results of nutritional tests on the A2 treatment biscuits (addition of 2% moringa flour) showed that the food was high in protein and suitable for consumption for people affected by stunting. Meanwhile, the saturated fat content is very low. This really supports the stunting program because saturated fat can inhibit the metabolism of omega-3 which functions for eye health and brain development.